Environmental Epidemiology – What’s at Stake: Open Issues and Methodologies - A Report from the 26th Annual International Society for Environmental Epidemiology (ISEE) Conference - Carugno, Michele (La Medicina del Lavoro, 2015)
At the end of last August, the University ofWashington (UW) in Seattle welcomed over 1,100 attendees at the 26th Annual ISEE Conference - “From Local to Global: Advancing Science for Policy in Environmental Health”...